Bibliometric analysis of ecopreneurship using VOSviewer and RStudio Bibliometrix, 1989–2019 - Guleria, Deepa; Kaur, Gurvinder (Library hi tech, 2021)
PurposeThis article offers a bibliometric analysis and explores the relationships among the documents on ecopreneurship by using relational techniques. The results highlight the publication trends; most cited documents, top contributing authors, countries and institutions with highest productivity and most contributing journals to the research field.Design/methodology/approachInitially, 216 documents were retrieved from the Thompson Reuters Web of Science Core Collection database with three document types: articles, review and book review. All the documents were considered for the analysis. Then VOSviewer and bibliometric analysis using R with an inbuilt utility Biblioshiny were used together for co-word analysis, co-citation network analysis, generating collaboration networks and also generating a unique three-field plot to analyze the evolution of a research field.FindingsThe results highlight the publication trends: most cited documents, top contributing authors, countries and institutions with highest productivity and most contributing journals to the research field. The network analysis of co-authorship, co-citation, keyword co-occurrence and bibliographic coupling reveals most prominent relationships between authors, documents, co-cited references, sources and countries for the available documents on the research field.Research limitations/implicationsThe study helps not only in expansion of knowledgebase on the research topic but also in understanding the evolution of the ecopreneurship to provide research support further in this area.Originality/valueEcopreneurship is an emerging field of research connecting ecology and entrepreneurship together, making it a potential research area. The contributions made to this research field from 1989 to 2019 serve as a core for conducting this analysis. The study is an effort to help in coordinating research network across countries, authors and affiliating universities.